Classification of pressure range based on the characterization of Escherichia coli cell disruption in high pressure homogenizer - Ramanan, Ramakrishnan Nagasundara; Tey, Beng Ti; Tau, Chuan Ling; Ariff, Arbakariya (Science Publications, 2009)
Problem statement: High pressure Homogenizer was used for cell disruption in many studies. But no work was carried out to study the characteristics of cell disruption in a wide range of pressure. Approach: The characteristics of Escherichia coli cell disruption was studied in Avestin small scale homogenizer by varying the operating pressure (50-1500 bar), cell concentration in the feed(1.39-12.51 g dry cell weight L-1) and number of passes (1-5 passes). Results: It was found that cell concentration between 1.39 g dry cell weight L-1 and 12.51 g dry cell weight L-1 has no effect on cell disruption while the pressure applied and number of passes gave different effects on cell disruption characteristics. In between 100 and 250 bar, the protein release was mainly due to point break. In this case, the variation in cell size was not significant with increasing number of passes and maximum protein release was not achieved even after many numbers of pass. However, selectivity of specific protein (interferon-α2b) was high as it is located predominantly in periplasmic region. In between 1000 and 1500 bar, the maximum protein release, maximum interferon-α2b release and drastic reduction of cell size was observed after the first pass. In subsequent passes, micronization of cell debris was observed but without much variation in protein release. There was no reduction in antigenicity of interferon-α2b even at 1500 bar. At 500 bar, the protein release and reduction of cell size were significantly increased with increasing number of passes. Conclusion: The pressure range for E. coli cell disruption was classified as low pressure range (100-250 bar), transition pressure (500 bar) and high pressure range (1000-1500 bar). The working pressure for the homogenizer could be selected by considering the operating cost and further downstream processing.